Comparative morphological, anatomical, micromorphological, and palynological studies on the genera Opopanax and Crenosciadium (Apiaceae) - Çetin, Özlem; Çelik, Mustafa (Phytotaxa, 2018)
In the present study, morphological, micromorphological, palynological and anatomical characteristics of the genera Opopanax and Crenosciadium are reviewed and compared. The genus Opopanax is distributed in southern Europe, the Mediterranean region and Western Asia, and it is represented by three species in Turkey. Crenosciadium is a poorly known monotypic genus from Turkey, recently treated as synonym in Opopanax. Expanded descriptions, phenology, geographic distributions, and images of habitus of Opopanax and Crenosciadium are given. The differences between the two genera are discussed. The pollen morphology of Opopanax and Crenosciadium is studied by SEM and LM. The palynological results confirmed the stenopalynous characteristic of the family Apiaceae, and revealed that the pollen grains of both genera are perprolate in shape. Also fruit surface ornamentation of both genera is typically striate, and epidermal cells are polygonal or elongated in one direction. Cross-sections of mature fruits are examined and a detailed anatomical description is presented. Mericarp shape and width are very useful characters for discrimination between Opopanax and Crenosciadium; mericarp ribs are also very significant characteristics to discriminate both genera. Our findings, together with previous molecular data, clearly indicate that Crenosciadium differs considerably from Opopanax, and therefore it should be accepted at genus rank.